Genetic Analysis of Reciprocal Crosses of Silkworm in New Iranian Lines and Hybrids - Shahla Nematollahian; Seyed Hossein Hosseini Moghaddam; Babak Rabiei; Seyed Ziaeddin Mirhoseini (پژوهشهای علوم دامی ایران)
Introduction: Commercial silkworm hybrids result from the controlled crossing of the Japanese-shaped parent with the Chinese-shaped parent (direct cross) and vice versa (reverse cross). Suppose the silkworm hybrids resulting from direct and reverse crossing have a large difference in the performance of the important productive, reproductive, and viability characteristics. In that case, they are not suitable for supply to the farmers. In this research, to identify the hybrid pairs with the least differences, the traits of 72 reciprocal hybrids (36 mating pairs) were tested by statistical methods. These results will be used for the final selection of commercial hybrids. Also, the genetic analysis of reciprocal hybrids and the estimation of genetic parameters in each of the mating programs were done separately using line × tester analysis. Materials and Methods: The current research was done at the Iran Silk Research Center by carrying out two mating programs in the form of line-tester crosses between six Chinese lines (IRA2, IRA4, IRA6, IRA8, IRA10, and IRA12) with six Japanese lines (IRA1, IRA3, IRA5, IRA7, IRA9, and IRA11). Six lines with dumbbell-shaped cocoons (Japanese) and six lines with oval-shaped cocoons (Chinese) were crossed bilaterally. All lines (12 genotypes) and 72 hybrids (36+36) were reared in a completely randomized design with 4 replications. All stages of hatching and rearing of silkworm lines and hybrids in this project were done in the same way based on standard methods. The studied traits including the number of cocoons per liter, cocoon weight per liter, best cocoons percentage, middle cocoons percentage, cocoon weight per 10,000 larvae, hatchability percentage, cocoon weight, cocoon shell weight, cocoon shell percentage, and pupation rate were recorded and analyzed by applying of GLM procedure of SAS software. Line×tester analysis was applied to study the reciprocal crossing effect and estimate genetic parameters. Gene effects, heritability, σ2gca/σ2sca, and Baker’s ratio were investigated by applying of IML procedure of SAS software. Results and Discussion: The results of the comparison of reciprocal hybrids based on the total difference (∑D) showed that this parameter was more than the total average in 14 pairs of hybrids. Therefore they could not be selected for commercial level. In the other 22 pairs, either none of the traits or at most one trait had a significant difference (P<0.05). The results showed that the characteristics of cocoon weight and cocoon shell weight were more affected by reciprocal crossing. On the other hand, the number of cocoons per liter, the hatchability percentage and the middle cocoon percentage were higher in Chinese mother hybrids than in Japanese mothers. For other traits (weight per liter, cocoon weight per 10,000 larvae, pupation percentage, good cocoon percentage and pupation percentage), Japanese mother hybrids were almost superior. The comparison of crosses effect in Japanese-shape lines and Chinese-shape testers with Chinese-shape lines and Japanese-shape testers showed that four traits (cocoon weight, cocoon shell weight, cocoon shell percentage and cocoon weight per 10 thousand larvae) and for the interaction effect (line × tester), three Traits (cocoon weight, cocoon shell percentage and pupation rate) were most affected by the substitution of parents. The values of additive genetic variance, Baker's coefficient, ratio σ2gca/σ2sca and heritability in four studied traits including cocoon weight, cocoon shell weight, cocoon shell percentage and number of cocoons per liter showed that these traits are under additive genetic effect. Moreover, they had a higher value in Chinese mothers than the Japanese mother crosses. The trait of cocoon weight per 10,000 larvae was also controlled by non-additive genetic effects, and the substitution of parents did not affect their genetic parameters. The pupation rate in the direct crosses was due to additive genetic effects, but in the reverse crosses was affected by non-additive genetic effects. In general, the narrow sense heritability for all traits was higher in Chinese-shape than in Japanese-shape mothers. Conclusions: In the present study, similar and close performances of the Chinese mother and Japanese mother hybrids were determined except for cocoon weight and cocoon shell weight which was different in almost 33% of reciprocal hybrids. The crosses effect in the line × tester ANOVA supported the result of mean comparison for reciprocal hybrids evaluation. Further field investigations can be carried out to select the hybrids suitable for different geographical conditions.